The Status Of Ramadan Fasting Observed By Hemodialysis Patients From An Islamic Perspective - Aifanisa Rahman; Wahyudi Rahman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The month of Ramadan is a special time for Muslims to worship, erase sins, and gain the rewards and pleasure of Allah SWT. Shaum or fasting, the primary worship during this month, involves abstaining from things that invalidate the fast. However, fasting is not intended to be difficult, as stated in the Qur'an, Surah Al-Baqarah: 185, which emphasizes ease rather than hardship in fasting. Besides its spiritual aspects, fasting also has health benefits, such as helping patients with obesity and heart disease. For patients with chronic kidney disease who require hemodialysis, fasting can be particularly challenging. Hemodialysis is a life-saving method that involves cleaning the blood outside the body. In Islam, there are principles of ushul fiqh that provide rukhsah or legal concessions for those who face difficulties in fulfilling religious obligations due to certain conditions. However, if a kidney failure patient insists on fasting despite having been granted rukhsah, this is known as azimah. This study aims to explore the status of azimah for hemodialysis patients who choose to fast from an Islamic perspective. Using a qualitative approach through literature review and in-depth interviews with fiqh experts, this research seeks to understand the legal implications and medical conditions involved. The results are expected to provide clearer insights into the practice of fasting for hemodialysis patients within the context of Islamic jurisprudence.